2023
DOI: 10.3390/d15040481
|View full text |Cite
|
Sign up to set email alerts
|

Detection and Evaluation of Environmental Stress in Winter Wheat Using Remote and Proximal Sensing Methods and Vegetation Indices—A Review

Abstract: Climate change has a significant impact on winter wheat (Triticum aestivum L.) cultivation due to the occurrence of various environmental stress parameters. It destabilizes wheat production mainly through abiotic stresses (heat waves, drought, floods, frost, salinity, and nutrient deficiency) and improved conditions for pest and disease development and infestation as biotic parameters. The impact of these parameters can be reduced by timely and appropriate management measures such as irrigation, fertilization,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 237 publications
1
12
0
Order By: Relevance
“…Furthermore, results revealed that soil properties, particularly Ca, Mg, K, and clay, have a moderate positive correlation with wheat crop height. Similar findings from other studies have revealed that an abundance of soil chemical properties such as K, Mg, and Ca have an influence on the wheat crop height throughout the growth period [7,21,59]. Other studies also demonstrated that the clay content, silt%, and pH values are more significant factors influencing plant growth [8,104].…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Furthermore, results revealed that soil properties, particularly Ca, Mg, K, and clay, have a moderate positive correlation with wheat crop height. Similar findings from other studies have revealed that an abundance of soil chemical properties such as K, Mg, and Ca have an influence on the wheat crop height throughout the growth period [7,21,59]. Other studies also demonstrated that the clay content, silt%, and pH values are more significant factors influencing plant growth [8,104].…”
Section: Discussionsupporting
confidence: 81%
“…The influence of intra-field soil physiochemical properties' variation and meteorological conditions are key factors on crop development across various crop stages. Other detrimental effects on wheat growth include abiotic stresses such as droughts, frost, waterlogging, salinity, high temperatures, and other natural calamities [20,21]. The biotic factors, which include the infestation of diseases, competing weeds, and pests, are common challenges for crop development [22][23][24][25].…”
Section: Introductionmentioning
confidence: 99%
“…This finding suggests that during the overwintering stage, characterized by the winter wheat's relatively strong cold resistance, a prolonged period of low temperature and multiple occurrences of extreme cold events accompanied by wintery precipitation can have a positive impact on winter wheat yield. This positive impact may be attributed to several factors, such as preventing premature transition to more cold-sensitive growth stages (Kosová et al 2008), facilitating the accumulation of dry matter in wheat, and enhancing resistance to pests and diseases (Guo and Huang 2009, Gaudet et al 2011, Vanková et al 2014, Skendžić et al 2023. In contrast, warm temperatures and an increased frequency of extreme heat events tend to have negative impacts on winter wheat yield.…”
Section: Discussionmentioning
confidence: 99%
“…Soil physical and chemical properties including texture, phosphorus (P), nitrogen (N), potassium (K), sodium (Na), calcium (Ca), magnesium (Mg), and pH influence crop growth. The essential soil physio-chemical properties for crops occur in low concentration levels within arid and semi-arid environments, which has a negative impact on crop growth [4]. Other factors that impede crop development include droughts, frost, waterlogging, salinity, high temperatures, diseases, weeds, and pests infestation [4].…”
Section: Introductionmentioning
confidence: 99%